2022
DOI: 10.3390/info13120562
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Construction of Knowledge Graphs for Research-Performing Organizations

Abstract: Research-Performing Organizations (e.g., research centers, universities) usually accumulate a wealth of data related to their researchers, the generated scientific results and research outputs, and publicly and privately-funded projects that support their activities, etc. Even though the types of data handled may look similar across organizations, it is common to see that each institution has developed its own data model to provide support for many of their administrative activities (project reporting, curricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Ontology plays a pivotal role in shaping the architecture of modern data management systems, particularly in contexts that require the integration of diverse and complex data sets [49,50]. At its core, ontology is a structured framework that defines the relationships between various entities and concepts within a particular domain.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Ontology plays a pivotal role in shaping the architecture of modern data management systems, particularly in contexts that require the integration of diverse and complex data sets [49,50]. At its core, ontology is a structured framework that defines the relationships between various entities and concepts within a particular domain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of ontology in data management enables advanced querying capabilities, making it possible to ask complex questions that span multiple data sets and types [53,57,58]. For instance, investigators could query the relationship between a DNA sample found at one crime scene and digital evidence from another, all within the same ontological framework [36,42,49]. This is particularly useful in cases involving serial crimes or organized criminal networks, where the ability to link seemingly unrelated pieces of information can be crucial for solving issues.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation